Statistical correlations on the emissions of volatile odorous compounds from the transfer stage of municipal solid waste. (15th March 2019) - Chang, Huimin; Tan, Haobo; Zhao, Yan; Wang, Ying; Wang, Xuemei; Li, Yanxia; Lu, Wenjing; Wang, Hongtao
Highlight: Ninety-six air emission samples were obtained during one-year monitoring. Ethanol, dimethyl disulfide and methyl mercaptan were key compounds in odor pollution. Correlation analysis applied to identify the relationship among odorous compounds. Ethylbenzene has correlation coefficients >0.5 with 25% of identified compounds. No representative compound was identified in the release rate calculation. Abstract: Odor pollution from treatment facilities and municipal solid waste (MSW) has caused wide public concern. Odorous compounds released from these facilities possess complex composition. Therefore, identifying typical odorous compounds and using their release rates to estimate those of other compounds may simplify the monitoring and evaluation of odor pollution. This study investigates the correlations of the release data of odorous compounds from a statistical perspective. For 12 months, we conducted in site monitoring in an MSW transfer station once each month to obtain 96 emission samples, and over 100 odorous compounds were quantified for each sample. Oxygenated compounds had considerable high release rates throughout the period, and ethanol was the dominant compound. Ethanol, dimethyl disulfide and methyl mercaptan were the top key compounds that contributed to the odor activity value. Correlation analyses within and across the categories showed that only a few compounds in saturated hydrocarbons and aromatic compounds had strong correlations with release rate. The coefficient of correlation between ethylbenzene and 19 other compounds, which covered only 25% of all the identified compounds in this study, was >0.5. These results show that representative compounds cannot be used in the calculation of release rate during the transfer stage.